Passing-skill training vs. small-sided games for improvement of side-foot kick accuracy among youth female soccer players - Carlsson, Tomas; Broman, Joakim; Isberg, Jenny; Carlsson, Magnus (Frontiers in Sports and Active Living, 2025)
This study compared the effectiveness of a passing-skill training (PST) concept (theory lectures, passing-skill training, and external- and internal-focus feedback) and three-a-side small-sided games (SSG) on improving side-foot kick accuracy among youth female soccer players. Seventeen youth female soccer players (age: 12.7 ± 0.8 years) completed the pre-post-intervention study, where the pre- and post-tests included three 10-m passing accuracy tests with increasing level of complexity: (1) stationary ball with a fixed target (SBFT), (2) rolling ball with a fixed target (RBFT), and (3) rolling ball with a moving target (RBMT). Based on the pre-tests, the participants were matched into the PST group or the SSG group. The training consisted of nine 30-min sessions for both groups during a period of 4.5 weeks. During the intervention, the PST group significantly improved the side-foot kick accuracy across all three tests. In contrast, the SSG group showed no significant change in passing accuracy in either the RBFT test or the RBMT test; however, their side-foot kick accuracy was significantly reduced in the SBFT test. There were significant between-group differences in side-foot kick accuracy across all three tests after the intervention, where the PST group had a greater side-foot kick accuracy than the SSG group. In conclusion, results indicate that the PST concept significantly enhances passing accuracy across all tested variables, unlike SSG, suggesting PST's superiority in technical skill development.